Analysis Cause of Automatic Voltage Regulator Damage to the Genset in KP Hiu 06 Owned the Ministry of Marine and Fisheries - Sobri Sobri; Ade Hermawan; Edwin Haryanto; Istianto Budhi Rahardja (Journal of Applied Sciences and Advanced Technology, 2019)
AVR on an electric generator is a device that serves to maintain the stability of the generator output voltage. KP Shark 06 suffered AVR damage twice in 2017 which affected the operations of the ship so it is necessary to analyze the cause of the damage. The steps to analyze the causes of AVR damage starts from the factor of overload on the electricity generator, the working condition of the electric generator and the motor driving factor of the electric generator. Based on observations and calculations of the ship's electricity load, it is known that there is no overload of electric generators, ie the average per day / hour of power used is 6,009.75 Watt, where the available power is 17,600 Watt (generator efficiency 34.14%). While the work of the generator is observed normally based on the results of the measurement of the electric current produced by the generator. It was concluded that the cause of AVR damage was due to the generator driving motor which experienced a decrease in performance so that when subjected to electric load the engine rotation experienced instability which caused voltage fluctuations where this caused the AVR to work abnormally resulting in AVR damage. After repairs to the generator drive engine during ship docking, the engine rotation of the electric generator drive motor becomes more stable and the working function of the AVR becomes more normal.